(untitled) (Eurasian Journal of Humanities and Social Sciences, 2021)
Distance Education today is one of the most commonly used types of educational delivery method. Almost every major and medium size university around the world has some kind of distance education services, regardless of the subjects taught. In this paper, I intend to discuss instruction such as seminars, lectures and direct classroom instruction which can be shared by distant institutions. Time differences between two distant institutions can be overcome by employing the satellite technology or recording facilities of institutions. Immediate presence of an instructor in the classroom is always sought after. However, the screen where one student can interact with an instructor provides no less opportunity.